The Principle of Lex Favor Reo in Moral Crimes: A Study of the Legal Implications of the Transitional Period of the National - Ika Yuliana Susilawati; Ahwan Ahwan (Rechtsvinding, 2026)
The transitional period following the implementation of the National Criminal Code (KUHP) has raised issues regarding the application of the Lex Favor Reo principle to changes in the provisions of moral offenses. This normative legal research aims to outline the criteria for determining the most favorable rules and analyze the legal effectiveness of applying this principle during the transitional period of the National Criminal Code. The research was conducted using a regulatory and contextual approach, utilizing primary and secondary legal materials analyzed qualitatively and prescriptively through systematic, contextual, and comparative interpretation. The results indicate that determining the most favorable rules cannot be based solely on quantitative calculations of criminal penalties but must be conducted in a hierarchical manner through three dimensions of analysis: criminalization, procedural, and punitive. The application of the Lex Favor Reo principle creates legal implications in the procedural aspect, affecting the use of the right to file a complaint and the withdrawal of a complaint, which determine the continuity of the legal process. In the penal aspect, it also raises the possibility of implementing alternative punishments that are more favorable to the perpetrator. Thus, the principle of lex favor reo during the transitional period of the National Criminal Code must be understood multidimensionally, taking into account the full legal consequences arising from the changes in the regulation of crimes against morality, thereby ensuring legal certainty, justice, and uniform application of the law in criminal practice.